Antioxidant and antimicrobial activity of blends of propolis samples collected in different years. (June 2021) - Peixoto, Marta; Freitas, Ana Sofia; Cunha, Ana; Oliveira, Rui; Almeida-Aguiar, Cristina
Abstract: Propolis is a complex mixture of resinous and balsamic material collected by bees from various plant sources which is then processed by salivary enzymes and mixed with other substances like beeswax. This natural product has several biological activities that may provide a wide range of applications. However, propolis low productivity and high diversity hamper its full and efficient use. In order to increase propolis availability and contribute to its standardization, essential for the manufacture of marketable products, blends of propolis were prepared with ethanol extracts of samples harvested from a Portuguese apiary over 2011 to 2015. These mixtures were chemically characterized in terms of total polyphenols and flavonoids, and tested for antioxidant potential and antimicrobial properties. The mixtures of propolis ethanol extracts generally show similar or better bioactivities than individual extracts, possibly due to synergisms between bioactive compounds. Our results suggest that blends of propolis samples from different years can retain or even potentiate the bioactivities of individual samples, namely antioxidant and antimicrobial activities. Therefore, blending could be a possible way of making a better and more efficient use of propolis and simultaneously contribute to its normalization, allowing large scale applications and adding more value to this remarkable natural product. Highlights: Ethanol extracts of propolis collected over five years used to make mixtures. Blends of propolis potentiate some bioactivities, with no loss of potential. The good bioactivities of blends anticipate a wider use and valorization for propolis.